Can Natural Laws be Derived from Sociability?. (23rd May 2018) - Coyle, Sean
Abstract: The article questions whether it is possible to derive natural laws from human sociability. It examines the work of Aristotle, Augustine and Aquinas, and concludes that there are certain natural laws that can be derived from the social character of human beings. Some of these hold across all societies and at all times (semper et ad semper) whereas others hold only in general but are subject to exceptions (semper sed non ad semper). The article concludes by confronting an anti‐social and immoralist challenge to the idea of natural laws of sociability.